Model Survival Nonparametrik Pada Data Rawat Inap Pasien Diare di Puskesmas Indralaya - Amran, Ali; Faruk, Alfensi (Jurnal Matematika; Vol 5 No 2 (2015), 2015)
This research aimed to (1) estimate the survival functions, and (2) investigate the effect of some covariates toward the survival time  from hospitalization time data in Public Health Center of Indralaya. The research subjects consisted of all the diarrhea patients who were hospitalized within the period from January 1, 2014 to June 30, 2014. The patient's characteristics were sex, age, job, and disease status. The result showed that the lowest probability of a patient will be out of hospitalization was on the fourth day and the highest probability was on the fifteenth day. In order to find the best model, some statistical tests were also conducted in this research.
Keywords: Survival Model; Time of Hospitalization; Cox Regression